Designing Syllabus and Instructional Materials for ESP Students of Online English Conversation Course - Noni Mia Rahmawati; Khoiriyah Trianti (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2021)
Online learning is believed to have many benefits for both the students and instructors. It is highly possible for an English conversation course for ESP students to perform the teaching and learning processes virtually. This study was carried out to design the syllabus and instructional materials for an online English conversation course for the ESP students of the business administration program. The initial step was performing needs analysis by using a questionnaire as the instrument. The results attained from the needs analysis was strengthened by interviewing the students. From the results of the needs analysis and interview, eight business-related topics were selected for 14 meetings. The learnings activities focused on the students’ oral business communication skills and focused on their written business communication skills. Visual aids in the form of videos and pictures were used to accompany the instructions given to the students. Expert validation was also carried out as a review of the designed syllabus and instructional materials. Students’ final feedback in the form questionnaire was also performed to get their perceptions on several aspects of the developed materials, learning activities, and assignments. The final product of the syllabus and instructional materials were published on the university’s LMS.